Study the Effect of Educational Activities “Exercises” to Improve Some Offensive Skills of Wheelchair Basketball Players Indirectly - Jawad Kadhim Almayah, Sanaa (International Journal of Psychosocial Rehabilitation, 2020)
The present study aims at investigating the effect of educational activities “Exercises” to improve some offensive skills of Wheelchair Basketball Players indirectly. The study significance lies in focusing on the importance of Kinesthetic learning methods and the role of these methods in teaching offensive skills to beginner wheelchair basketball players, just by being help them to improve the skills in accordance with these educational exercises as well as the indirect method, its effectiveness and significance showed that they have an importance in conveying the right information during performance, the statement of the problem was manifested in the presence there learning basic offensive skills does not live up to the level of ambition and because of the lack of experimentation purposeful exercises and the successful scientific method of it indirect method.